Fault resistance and soil resistivity influence on the impedance based methods for locating faults. a comparative analysis (2010)
The influence of the soil resistivity and the fault resistance is considered in this paper where a comparison of a well defined impedance based method for locating faults is presented. Tests were performed in a real power distribution system, using soil resistivity measurements and a range of fault resistances commonly found in such systems. According to the results in a 34kV power distribution system, it is notice that the soil resistivity models which best represents the real systems are those which give better results in the fault location. Additionally, the higher the fault resistance is, the lower the performance index is, showing the influence of this variable. Finally, the influence of the soil resistivity in the distance estimation in such faults where the zero sequence current is different from zero is also analyzed in this paper